2014
DOI: 10.4238/2014.october.7.2
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte/macrophage β2-AR as a target of antisympathetic excitation-induced atherosclerotic progression

Abstract: ABSTRACT. The aim of this study was to determine whether monocyte/macrophage β2-AR could act as the therapeutic target of antisympathetic excitation-induced atherosclerotic progression. Cultivated human THP-1 cells were divided into different groups and incubated with isoprenaline, metoprolol, propranolol or β2-AR blocker for 24 h, together with oxidized low-density lipoprotein (ox-LDL). Afterwards, each group was analyzed for C-C chemokine receptor type 2 (CCR2) expression, monocyte chemotactic protein 1 (MCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Here, we showed that propranolol downregulated HLA-DR in M1 conditions, an event that supports the M2-like profile generated by the β-AR signaling antagonism. Our results on the ability of propranolol to affect the M1 pro-inflammatory phenotype are consistent with finding by Guo et al, who found that propranolol inhibits the pro-inflammatory MCP-1 and CCR2 protein expression of macrophages [37].…”
Section: Discussionsupporting
confidence: 93%
“…Here, we showed that propranolol downregulated HLA-DR in M1 conditions, an event that supports the M2-like profile generated by the β-AR signaling antagonism. Our results on the ability of propranolol to affect the M1 pro-inflammatory phenotype are consistent with finding by Guo et al, who found that propranolol inhibits the pro-inflammatory MCP-1 and CCR2 protein expression of macrophages [37].…”
Section: Discussionsupporting
confidence: 93%
“…These differences may be due to the lack of specificity of norepinephrine and epinephrine treatment and activation of multiple adrenergic receptor subtypes. Further, β2AR stimulation was previously shown in THP-1 human monocytic cells to increase CCR2 expression and migration through an undefined mechanism (30), whereas another study demonstrated that treatment of THP-1 cells with cAMP-elevating agents, including PDE3 inhibitors and dibutyryl cAMP, decreased both CCR2 expression and CCL2-mediated migration (31). These results may suggest that Gα s protein-dependent β2AR signaling acts to repress CCR2 expression.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, reducing the number of M2-type macrophages in plaques or the degree of M2-type polarization and preventing nonapoptotic death (such AS focal death) including cell membrane rupture induced by excessive lipid phagocytosis of M2-type macrophages may be the important mechanism of the above-mentioned β-AR blocker inhibiting the progression of AS. Previous studies (42) and other studies (40)(41)(42) of this research group showed that β-AR blockers with different degrees of blocking effect on β2-AR: including metoprolol (43,44), propranolol (44)(45)(46), carvedilol (47) and nebivolol (48,49) had significant anti-AS effects. Therefore, reducing the number of M2-type macrophages in plaques or the degree of M2-type polarization and preventing non-apoptotic death (such AS pyroptosis) including cell membrane rupture induced by excessive lipid phagocytosis of M2-type macrophages may be the important mechanism of the above-mentioned β-AR blocker inhibiting the progression of AS.…”
Section: Discussionmentioning
confidence: 66%